Miscellaneous Studies - Poebel, A. (2000)
1. The City of Esâ (Dûr-Kuri-Galzu) — 2. The “Schachtelsatz” Construction of the Narâm-Sin Text RA XVI 157f. — 3. Murnisqu and Nisqu in Cylinder A of Gudea — 4. The. Formula of the 16th Year of Samsu-Ditana — 5. The Use of Mathematical Mean Values in Babylonian King List B; Doll. 3.50.